Accelerated (18 mW/cm2) Corneal Collagen Cross-Linking for Progressive Keratoconus. Issue 11 (November 2015) - Unknown
Abstract : Purpose: The aim of this study was to determine the efficacy of accelerated riboflavin–ultraviolet A–induced corneal collagen cross-linking (CXL) (irradiance of 18 mW/cm 2 for 5 minutes). Methods: In this study, we retrospectively reviewed the charts and anterior segment data of patients after accelerated CXL. Visual, topographic, pachymetry, and densitometry data were extracted and analyzed before surgery and at follow-up (minimum 12 months) after treatment. Results: A total of 28 eyes of 20 patients (mean age, 28.1 ± 8.1 years) were included in this study. The mean follow-up time was 21.7 ± 7.2 months (range, 12–34 months). No statistically significant changes were found in the mean corrected distance visual acuity, corneal astigmatism, Kmean, Kflat, Ksteep, corneal pachymetry (at the apex and at the thinnest point), and corneal densitometry at follow-up. A significant reduction of Kmax, index of surface variance, index of vertical asymmetry, and Km of the posterior corneal surface (Km B ) was observed (Kmax: P = 0.018; index of surface variance: P = 0.016; index of vertical asymmetry: P = 0.038; Km B : P = 0.008). No complications were reported during the postoperative follow-up period in this study. Conclusions: Based on a mean follow-up time of 21.7 months, accelerated CXL (18 mW/cm; 5 minutes) is effective in stopping the progression of keratoconus without raising any safety concerns. Improvement in Kmax and stabilization of corrected distance visual acuity were noted after treatment. However, prospective studies with longer follow-up using different accelerated CXL settings are needed to validate these findings.